Ultrasonic Investigation of α-Amino Acids with Aqueous Solution of Urea at Different Temperatures: A Physicochemical Study - Malik, Nazia; Khan, Azhar U.; Naqvi, Saeeda; Arfin, Tanvir (Journal of Applied Solution Chemistry and Modeling, 2016)
The present paper reflects the ultrasonic investigations for exploring the inter-ionic interactions of various concentrations of α-amino acids such as L-Arginine, L-lysine monohydrochloride, and L-histidine in aqueous solutions of urea over a wide ranges of temperatures (298.15 to 323.15) K under atmospheric pressure. It also represent the detail showing that molecular interactions between the a-amino acids and urea has much dissociation of proteins in the solvent mixture. The study of ultrasonic speed and sound velocity were successfully preformed on the liquid ternary mixtures. With the help of the above mentioned parameter, the values of isentropic compressibility, change in isentropic compressibility , relative change in isentropic compressibility , relative association , specific acoustic impedance , and apparent molal isentropic compressibility were calculated. These parameters have been examined in term of the molecular associations such as ion-ion, ion-solvent, solute-solvent, solute-solute etc., and briefly described in terms of the structure-making ability corresponding to a-amino acids in the urea. Efforts have been taken to explore the dependency of the outcomes related to temperature and concentration.